A multi-centre, randomised trial for diagnostic efficacy of the automatic breast volume scanner ultrasound for breast cancer screening in China - Xu, Ying; Xu, Yali; Shen, Songjie; Mao, Feng; Zhang, Xiaohui; Zhang, Yanna; Lin, Yan; Zhou, Yidong; Sun, Qiang (Frontiers in Oncology, 2025)
IntroductionThe US plays a crucial role in screening Asian women for breast disease. ABUS offers several advantages over traditional HHUS, including quicker examination, objectivity, and the ability to store and reconstruct images. This study marks the first large-scale opportunistic screening of ABUS in the population.MethodsBetween January 1, 2016, and December 31, 2019, 10,537 women aged 35–75 years from nine districts were randomly assigned to either HHUS or ABUS groups. Diagnostic methods were quantified, and comparisons were made using the Chi-square test.ResultsThe screening groups consisted of 5,445 participants for HHUS and 4,936 for ABUS. The HHUS and ABUS groups identified 90 carcinomas and 292 benign lesions or 71 carcinomas and 178 benign lesions, respectively. SE), SP, AC, PPV, and NPV for HHUS were 51.11%, 93.84%, 93.13%, 12.23%, and 99.13%, respectively, while for ABUS, they were 66.20%, 93.77%, 93.38%, 13.43%, and 98.98%. The area under the curve (AUC) values for HHUS and ABUS were 0.72 (95% CI: 0.67–0.78) and 0.86 (95% CI: 0.82–0.91), respectively, indicating superior diagnostic performance of ABUS over HHUS (Delong test p < 0.05).DiscussionABUS is user-friendly, requires minimal training, reduces reliance on examiner experience, and demonstrates potential for superior sensitivity compared to HHUS in breast cancer screening.